1998
DOI: 10.1093/emboj/17.9.2651
|View full text |Cite
|
Sign up to set email alerts
|

Dbp5p, a cytosolic RNA helicase, is required for poly(A)+ RNA export

Abstract: The DBP5 gene encodes a putative RNA helicase of unknown function in the yeast Saccharomyces cerevisiae. It is shown here that Dbp5p is an ATP-dependent RNA helicase required for polyadenylated [poly(A) ⍣ ] RNA export. Surprisingly, Dbp5p is present predominantly, if not exclusively, in the cytoplasm, and is highly enriched around the nuclear envelope. This observation raises the possibility that Dbp5p may play a role in unloading or remodeling messenger RNA particles (mRNPs) upon arrival in the cytoplasm and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
183
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(196 citation statements)
references
References 68 publications
2
183
1
Order By: Relevance
“…Our data indicate that purified recombinant DDX1 does not possess RNA unwinding activity, but the immunoprecipitated DDX1 complexes exhibit such activity to unwind a substrate with poly(A) overhang. This finding implies that, just like eIF-4A (20) and Dbp5p (27), DDX1 requires co-factors to unwind RNA duplexes. It was also demonstrated that DDX1 exhibits its RNA unwinding activity only for a specific RNA substrate, as previously observed in the case of An3 (37).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our data indicate that purified recombinant DDX1 does not possess RNA unwinding activity, but the immunoprecipitated DDX1 complexes exhibit such activity to unwind a substrate with poly(A) overhang. This finding implies that, just like eIF-4A (20) and Dbp5p (27), DDX1 requires co-factors to unwind RNA duplexes. It was also demonstrated that DDX1 exhibits its RNA unwinding activity only for a specific RNA substrate, as previously observed in the case of An3 (37).…”
Section: Discussionmentioning
confidence: 94%
“…Two sets of RNA fragments, A and B or C and D, were annealed in buffer containing 10 mM Tris-HCl, pH 7.5, and 100 mM NaCl after boiling for 5 min and cooling down gradually to 30°C. RNA unwinding assay was performed as described (27). 40 fmol of duplex RNA in a 10-l reaction containing 17 mM HEPES, pH 7.5, 150 mM KCl, 2 mM DTT, 1 mM MgCl 2 , 5% glycerol, 0.3% PEG 8,000, 1 mM ATP, 40 units of RNasin, 1 g of tRNA, and the indicated proteins were incubated at 37°C for 20 min.…”
Section: Amino Acid Sequence Analysis By Lc/ms/ms-followingmentioning
confidence: 99%
“…Our demonstration that NOH61 exhibits the capacity to hydrolyze ATP is not surprising, because many proteins that possess the superfamily II helicase domain have been shown previously to be ATPases. However, NOH61 ATPase activity displayed only a modest stimulation (1.6-to 3.9-fold) in the presence of polynucleotides, in apparent contrast to other DEAD-box proteins (for example, see proteins Dbp5p [Tseng et al, 1998] and Ded1p [Iost et al, 1999]). Nevertheless, it should be noted that there are several viral proteins whose ATPase activity is stimulated only weakly by nucleic acids (Kadare and Haenni, 1997).…”
mentioning
confidence: 88%
“…Dbp5 (DDX19 and DDX25 in vertebrates) represents a furthe r emerging paradigm of how DEAD box proteins are regulated: through local activation. It interacts with the transcription machinery and with nascent RNPs 74,75 to mediate mRNA export from the nucleus 110,111 , and it has also been implicated in the termination of translation 112,113 . Although it is not known whether Dbp5 remains bound to mRNAs from transcription to export, as eIF4AIII does, elegant studies have demonstrated that Dbp5 activity must be highly localized during mRNA export 114,115 .…”
Section: Nuclear Specklesmentioning
confidence: 99%